Proposed Cape Krusenstern National Monument, Alaska : final environmental statement - United States. Dept. of the Interior. Alaska Planning Group. (Washington : Alaska Planning Group, Department of the Interior, 1974)
Cover title: Cape Krusenstern National Monument Bibliography: p. 457-461 Mode of access: Internet.